(3GdSajfI GdLGeYI dCfhGY GdYdhes - (3GdMSf Hf cQGeI GdLTej GdHjgbj, CHh SYjOs
(3ChdgG (B:s
(3CHhGH aj GdYde hGdYdeGA , HGH aj aVd GdYGde hGdYde, bGd Gddg JYGdi(B: (3gd jSJhj GdPjf jYdehf hGdPjf dGjYdehf s
(3BNQgG (B:s
(3hjfJgj HHGH (B" (3ai Cf GdYHGOI CaUd ef WdH GdeGd GdMdGd(B" (3hBNQ eG ajg ef MOjK QShd Gddg Udi Gddg Ydjg hSde(B: (3hdQcYJGf NajaJGf NjQ ef GdOfjG heG ajgG s
(3ocJHJ dNRGfI GdSdWGf CMeO Hf Ydj GdUdjMjs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdSjO eMeO Hf eMeO Hf ESeGYjd GdeWgQ GdNGUI HUfYGA (B(179) s
Keywords: (3GdeYGQa GdYGeIs